3(x - y)
3 (x - y)
3x over x + y
(x+y)/2
If x+y = 3 and y times x = 2 then y = 1.
x5 You have x*x*x*x*x just add up the amount of x's you have and put it after as an exponent Example: 3*3*3*3=34 y*y*y*y*y*y=y6
X=3. Y=4. pi=3.14. Answer: 37.68.
If you meant (45x^4)(y), then the answer is: (3)(3)(5)(x)(x)(x)(x)(y) If you meant 45 times x times 4 times y, then the answer is: (2)(2)(3)(3)(5)(x)(y)
3(x - y)
3 (x - y)
3x over x + y
0
(9) · (x) · (2/3) · (y) = 6 x y
When dividing fractions, multiply by the inverse of the fraction.That is, a/b divided by x/y = a/b times y/x = ay/bxFor example,2/5 divided by 3 = 2/5 x 1/3 = 2/152/5 divided by 1/3 = 2/5 x 3/1 = 6/55 divided by 3 = 5/1 x 1/3 = 5/35 divided by 1/3 = 5/1 x 3/1 = 15/1 (= 15)
-3X - 3Y x 8
X/3+Y There is no answer unless its equal to something X/3+Y=0 for example, or you have a value for the variables (1)/3+(2).
( 6x2 / y ) × ( y3 / 12x4) = 6x2y3 / 12x4y = y2 / 2x2